EFEKTIFITAS PROGRESSIVE MUSCLE RELAXATION (PMR) DAN RELAXATION BREATHING EXERCISE (RBE) TERHADAP TINGKAT FATIGUE DAN SELFCARE PASIEN GGK - Aniska Indah Fari; Yani Sofiani; Anwar Wardy Warongan (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Chronic kidney failure is a progressive and irreversible kidney disorder to maintain fluid and electrolyte balance and metabolism, with treatment given by hemodialysis. Long-term hemodialysis patients can cause fatigue in the patient's inability to fulfill selfcare needs. The intervention is in the form of non- pharmacological therapy in the form of relaxation. The purpose of this study was to determine the effectiveness of progressive muscle relaxation and relaxation breathing exercise on the level of fatigue and self care of patients with chronic renal failure. With the design of Randomized Clinical Trial (RCT) pre and post group three test, a sample of 30 respondents. Data collection tools are the Piper Fatigue Scale (PFS) questionnaire (Cronbach alpha = 0.646) and Fatigue Selfcare Management (Cronbach alpha = 0.930). The results showed that PMR intervention had different levels of fatigue (pvalue = 0,000) while selfcare (pvalue = 0.017) had no difference, in the RBE intervention there were differences in fatigue levels (pvalue = 0,000) while selfcare (pvalue = 0.048) had no difference, at PMR + RBE interventions have different levels of fatigue (pvalue = 0,000) and selfcare (pvalue = 0,000). PMR and RBE interventions are more effective to reduce fatigue and improve selfcare, so that it can be recommended for patients undergoing hemodialysis